(untitled) (The International Journal for Scientific Research, 2026)
This study examines the decision evaluation rule set out in Article 31 of the Saudi Companies Law and its effect on the liability of company managers and board members. It argues that the rule does not create immunity, but establishes a rebuttable presumption that the decision-maker performed the required duty when acting in good faith, without a personal interest, on an appropriately informed basis, and with a firm and rational belief that the decision serves the company’s interests. The study analyzes the rule’s relationship with the duties of care and loyalty, its application to action and inaction, its evidentiary effect, the limits of judicial review, and the consequences of losing protection. It concludes that protection depends on the quality of the decision-making process at the time of the decision rather than its subsequent economic outcome, and that rebutting the presumption does not dispense with proving fault, damage, and causation.